C1-Inhibitor Treatment Decreases Renal Injury in an Established Brain-Dead Rat Model. Issue 1 (January 2018) - Poppelaars, Felix; Jager, Neeltina M.; Kotimaa, Juha; Leuvenink, Henri G.D.; Daha, Mohamed R.; van Kooten, Cees; Seelen, Marc A.; Damman, Jeffrey
Abstract : Background: Kidneys derived from brain-dead (BD) donors have lower graft survival rates compared with kidneys from living donors. Complement activation plays an important role in brain death. The aim of our study was therefore to investigate the effect of C1-inhibitor (C1-INH) on BD-induced renal injury. Methods: Brain death was induced in rats by inflating a subdurally placed balloon catheter. Thirty minutes after BD, rats were treated with saline, low-dose or high-dose C1-INH. Sham-operated rats served as controls. After 4 hours of brain death, renal function, injury, inflammation, and complement activation were assessed. Results: High-dose C1-INH treatment of BD donors resulted in significantly lower renal gene expression and serum levels of IL-6. Treatment with C1-INH also improved renal function and reduced renal injury, reflected by the significantly lower kidney injury marker 1 gene expression and lower serum levels of lactate dehydrogenase and creatinine. Furthermore, C1-INH effectively reduced complement activation by brain death and significantly increased functional levels. However, C1-INH treatment did not prevent renal cellular influx. Conclusions: Targeting complement activation after the induction of brain death reduced renal inflammation and improved renal function before transplantation. Therefore, strategies targeting complement activation in human BD donors might clinically improve donor organ viability and renal allograft survival. Abstract : The study explores the protective effect of C1-inhibior on renal allograft function in a rat brain-death model. It suggests that high doses of C1-inhibitor significantly attenuates renal inflammation and improves organ viability. Supplemental digital content is available in the text.